2022
DOI: 10.1039/d1py01686e
|View full text |Cite
|
Sign up to set email alerts
|

Polymersomes with a smectic liquid crystal structure and AIE fluorescence

Abstract: A series of amphiphilic diblock copolymers PEG-TPE-b-PAChol containing a cholesterol-based smectic liquid crystal block PAChol and a tetraphenylethene AIEgen situated between hydrophilic PEG and hydrophobic PAChol blocks were prepared by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…They used both analytic and numerical approaches and focused on the competition between the extrinsic bending energy and two‐dimensional Frank free energy 48 . Recently, they reported that the smectic LC ordering in the membrane of elongated ellipsoidal or tubular polymersomes was preserved when a tetraphenylethene providing aggregation‐induced emission (AIE) fluorescence was situated between hydrophilic and hydrophobic LC blocks 49 . The performance of these LC polymersomes and cholesterol‐based NPs could be regulated by other AIEgens which can be excited by light with wavelengths longer than those of UV, and thus the NPs of LC BCPs can be designed as fluorescent carriers of drugs in the future.…”
Section: Traditional Solution Self‐assemblymentioning
confidence: 99%
“…They used both analytic and numerical approaches and focused on the competition between the extrinsic bending energy and two‐dimensional Frank free energy 48 . Recently, they reported that the smectic LC ordering in the membrane of elongated ellipsoidal or tubular polymersomes was preserved when a tetraphenylethene providing aggregation‐induced emission (AIE) fluorescence was situated between hydrophilic and hydrophobic LC blocks 49 . The performance of these LC polymersomes and cholesterol‐based NPs could be regulated by other AIEgens which can be excited by light with wavelengths longer than those of UV, and thus the NPs of LC BCPs can be designed as fluorescent carriers of drugs in the future.…”
Section: Traditional Solution Self‐assemblymentioning
confidence: 99%
“…Triblock BCP bearing a PEG group, a cholesteryl acrylate block and a tetraphenylethene AIEgen (aggregation-induced emission material) side group were synthesised by Zham et al [65]. The BCP was then self-assembled in a mixture of either dioxane/water or THF/water.…”
Section: Cholesteryl Polymer-based Nano-objects Showing Aggregation-i...mentioning
confidence: 99%
“…[3] Due to the stimuli-responsiveness, anisotropy and physiological medicine properties of LC NPs, they have received extensive attention in the fields of drug delivery, [4] functional nanomaterials [5] and so on. For example, Li et al [6] developed an LC nanoparticle with aggregation-induced emission (AIE) fluorescence group and cholesterol mesogen, which has the potential as imaging agents and drug carriers. Kasi et al [7] developed a brush gold LC nanoparticle containing the cholesterol mesogen, which successfully encapsulated the hydrophobic anticancer drug doxorubicin.…”
Section: Introductionmentioning
confidence: 99%